Analisis Pencatatan Penerimaan Dan Pengeluaran Kas (Studi Kasus Pada Siswa Paket C PKBM Aditya): Analysis of Cash Receipts and Expenditures (Case Study of Package C Students at PKBM Aditya) - Mas Muhamad Jamaludin (CV Warnak Johanna Nusantara, 2025)
This research is motivated by the importance of accurate recording of cash receipts and disbursements and supporting financial management at PKBM Aditya. This study aims to analyze the recording of cash receipts and disbursements at PKBM Aditya, especially for Package C students during the period from January to April 2025. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that recording of cash receipts and disbursements at PKBM Aditya is still done manually and has not been computerized. The problems found include errors in recording the amount of debit and credit in the cash diary in April 2025. This causes the balance and financial reports to be inaccurate every month. In addition, the division of recording tasks which is only carried out by one treasurer without internal control increases the potential for recording errors. This study applies a computerized recording system such as Zahir, Myob and division of tasks to avoid fraud in financial reports